2001
DOI: 10.1063/1.1427156
|View full text |Cite
|
Sign up to set email alerts
|

Giant photoresistivity and optically controlled switching in self-assembled nanowires

Abstract: We report the observation of giant photoresistivity in electrochemically self-assembled CdS and ZnSe nanowires electrodeposited in a porous alumina film. The resistance of these nanowires increases by one to two orders of magnitude when exposed to infrared radiation, possibly because of real-space transfer of electrons from the nanowires into the surrounding alumina by photon absorption. This phenomenon has potential applications in “normally on” infrared photodetectors and optically controlled switches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 132 publications
(78 citation statements)
references
References 5 publications
1
77
0
Order By: Relevance
“…Similar effect was previously reported by Kouklin et al 23 , who suggested that the wave functions of electrons in the AAOtemplated semiconductor (CdS) nanowires penetrate a short distance into the surrounding alumina as a result of photo-assisted process, where electrons get trapped at the sub-band energy levels and can no longer contribute to conduction.…”
Section: Resultssupporting
confidence: 71%
“…Similar effect was previously reported by Kouklin et al 23 , who suggested that the wave functions of electrons in the AAOtemplated semiconductor (CdS) nanowires penetrate a short distance into the surrounding alumina as a result of photo-assisted process, where electrons get trapped at the sub-band energy levels and can no longer contribute to conduction.…”
Section: Resultssupporting
confidence: 71%
“…Zinc selenide is one of the promising materials for the use in optoelectronic devices such as blue laser diodes [3], light-emitting diodes (LEDs) [4], optically controlled switches [5] and tunable mid-IR laser sources for remote-sensing applications [6]. Since the dimension of materials is believed to determine the optical, electronic, thermal and mechanical properties control of the size of the particles is very crucial [7]. In recent years, various types of 1D nanostructure, such as III-V, and II-VI group compounds, have been synthesized [8].…”
Section: Introductionmentioning
confidence: 99%
“…ZnSe is ideal material for blue-green laser diodes [1] [2], mid-IR laser sources for remote sensing applications [5], and in optically controlled switching devices due to its large photo resistivity [6]. Zinc selenide thin films had been fabricated by photochemical deposition (PCD) [7], chemical bath deposition (CBD) [8] [9] and electrochemical deposition (ECD) [10], but all these methods have Materials Sciences and Applications their own drawbacks including higher annealing temperatures for PCD, controlling rate of reaction for CBD and the use of only conductive substrates for ECD [7].…”
Section: Introductionmentioning
confidence: 99%